Strategy and Perception of Tomoro Blimbing Coffee Brand Equity - Siti Ulfatul Faizah; Tisa Reta Vianda; Sudarmiatin Sudarmiatin; Wening Patmi Rahayu (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the brand equity strategy and perception of Tomoro Coffee Blimbing based on four main dimensions: brand awareness, brand association, perceived quality, and brand loyalty. A descriptive qualitative approach was used through in-depth interviews with management, baristas, and customers. The data were then analyzed thematically through data reduction, presentation, and conclusion drawing. The results show that Tomoro Coffee's brand awareness is strongly formed through store expansion, social media activities, and a memorable slogan. Brand associations are perceived as modern, aesthetic, and closely related to youth lifestyles, although there is still a conflict between premium and economical images. Regarding quality perceptions, customers value consistent coffee taste and service, but perceived value is still influenced by promotions. Customer loyalty varies, with some indicating repeat visits due to quality, while others rely on promotions and situational needs. This study concludes that Tomoro Coffee's brand equity is quite strong, but needs to be strengthened with perceived value and fostering emotional loyalty. The implications of these findings can inform the development of marketing strategies and brand management in the increasingly competitive coffee shop industry.